Pengaruh Kompetensi Profesional Guru terhadap Prestasi Belajar Peserta Didik di SMP Islam Al Ulum Terpadu Medan - Mia Audina Naibaho; Mesiono Mesiono; Inom Nasution (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to determine the professional competence of teachers on student learning achievement at Al-Ulum Terpadu Islamic Middle School, Medan. This research uses a quantitative approach with a descriptive method using a questionnaire as a data collection instrument. The population in this study was 32 teachers, so the sample size in this study was 32 teachers, because the population was less than 100, based on Suharsimi Arikunto's opinion, the entire population was used (population study). The main data collection technique uses a 5 Likert scale answer choice form. Data is analyzed using simple linear regression to test the research hypothesis. Based on the data processing carried out, statistical testing resulted in Ho being rejected and Ha being accepted, which explains that there is an influence of teacher professional competence on student learning achievement. This is obtained from the results of the F test which shows Fcount is 19.072 and Ftable = (k-1; nk) namely (2-1; 32-2) = (1;30) = 4.17, so the value of Fcount > Ftable is 19.072 > 4.17 with a sig value. 0.001 < 0.05 which means there is an influence of teacher professional competence on student learning achievement in the F statistical significance test. Apart from that, a simple linear regression test was carried out to obtain the regression equation Y' = 105.683 – 1.44 1.44. However, if the teacher's professional competency value is 105.683 when X is 0, then student learning achievement will decrease by 0.144 for every one unit increase in %. Meanwhile, the remaining 61.1% is explained by other variables not studied.